The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1021/ic9708935
|View full text |Cite
|
Sign up to set email alerts
|

Lewis-Acid Properties of Technetium(VII) Dioxide Trifluoride, TcO2F3:  Characterization by 19F, 17O, and 99Tc NMR Spectroscopy and Raman Spectroscopy, Density Functional Theory Calculations of TcO2F3, M+TcO2F4- [M = Li, Cs, N(CH3)4], and TcO2F3·CH3CN, and X-ray Crystal Structure of Li+TcO2F4-

Abstract: Technetium(VII) dioxide trifluoride, TcO 2 F 3 , behaves as a Lewis acid toward the fluoride ion and acetonitrile forming M + TcO 2 F 4 -[M ) Li, Cs, N(CH 3 ) 4 ] salts and TcO 2 F 3 ‚CH 3 CN. Fluorine-19 NMR spectroscopy established that the TcO 2 F 4anion has a cis-dioxo geometry in CH 3 CN solution. Variable-temperature 19 F NMR studies of TcO 2 F 4and TcO 2 F 3 ‚CH 3 CN in CH 3 CN revealed that the one-bond couplings between 99 Tc and the two fluorine environments exhibit widely different degrees of quadru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
56
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 69 publications
17
56
0
Order By: Relevance
“…The dinuclear (dimeric) structure of these compounds consists of corner-shared octahedra with a bridging fluorine atom. Fluorine-bridging species [W 2 O 2 F 9 ] À (McFarlane et al, 1971;Buslaev, Kokunov, Bochkareva & Shoustorovich et al, 1972) (Casteel et al, 1998) were found in organic mediums, (CH 3 O) 2 SO, CH 3 CN. The controlled hydrolysis of hexafluorides of molybdenum, tungsten and rhenium also yielded the fluorine-bridged [M 2 O 2 F 9 ] À species (Hoskins et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The dinuclear (dimeric) structure of these compounds consists of corner-shared octahedra with a bridging fluorine atom. Fluorine-bridging species [W 2 O 2 F 9 ] À (McFarlane et al, 1971;Buslaev, Kokunov, Bochkareva & Shoustorovich et al, 1972) (Casteel et al, 1998) were found in organic mediums, (CH 3 O) 2 SO, CH 3 CN. The controlled hydrolysis of hexafluorides of molybdenum, tungsten and rhenium also yielded the fluorine-bridged [M 2 O 2 F 9 ] À species (Hoskins et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The Re-F bonds, which are trans posi tioned to Re=O, are much longer than Re-F cis (Δ = 0.135 Å). The two layer packing of structural units in crystal VII with the shortest distance О···О 3.065 Å, which exceeds the doubled van der Waals radius of oxygen (2.84 Å [22]), is similar to that in the Li[TcO 2 F 4 ] structure [23].…”
Section: Structure Of Monomeric Octahedral D 0 Re(vii)mono Oxo Complexmentioning
confidence: 61%
“…In accordance with the IR spectrum of [WO 2 F 4 ] 2À , the cis-dioxo isomer was definitively established in solution by this method. The cis-structure of [WO 2 F 4 ] 2À , as well as those of [MoO 2 F 4 ] 2À [6], OsO 2 F 4 [7], [TcO 2 F 4 ] À [8] and [ReO 2 F 4 ] À [9], were characterized by two 19 F NMR resonances (two triplets) of equal intensity associated with an A 2 X 2 spin system. In contrast, the trans-isomer would have all four fluorine ligands equivalent and the 19 F NMR spectrum would consist of a singlet.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, oligomerization in the case of d 0 transition metal fluoride compounds is common. For example, the fluorine-bridged species [W 2 O 2 F 9 ] À [11,20], [Mo 2 O 2 F 9 ] À [21], [Re 2 O 4 F 7 ] À , [Re 3 O 6 F 10 ] À [9], and possibly [Tc 2 O 4 F 7 ] À[8] have been observed in (CH 3 O) 2 SO and CH 3 CN. In all cases, the fluorine bridges are trans to oxygens in these anions.…”
mentioning
confidence: 99%
See 1 more Smart Citation